2020
DOI: 10.1371/journal.pone.0241753
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microvascular and morphological alterations in eyes with central retinal non-perfusion

Abstract: Purpose To evaluate the characteristics and morphological alterations in central retinal ischemia caused by diabetic retinopathy (DR) or retinal vein occlusion (RVO) as seen in optical coherence tomography angiography (OCTA) and their relationship to visual acuity. Methods Swept-source optical coherence tomography (SSOCT) and OCTA (Topcon, Triton) data of patients with central involving retinal ischemia were analyzed in this cross-sectional study. The following parameters were evaluated: vessel parameters, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…In the early stages of DR, microvascular damage, including the loss of pericytes and proliferation of endothelial cells, weakens the vascular walls, resulting in the formation of microaneurysms (MAs) and increasing the vascular permeability and pathologic neovascularization [6,7]. The breakdown of the blood-retinal barrier caused by a high concentration of inflammatory mediators and the leakage of MAs lead to the development of diabetic macular edema (DME), which is identified as a leading cause of vision impairment in patients with diabetes mellitus type 2 [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of DR, microvascular damage, including the loss of pericytes and proliferation of endothelial cells, weakens the vascular walls, resulting in the formation of microaneurysms (MAs) and increasing the vascular permeability and pathologic neovascularization [6,7]. The breakdown of the blood-retinal barrier caused by a high concentration of inflammatory mediators and the leakage of MAs lead to the development of diabetic macular edema (DME), which is identified as a leading cause of vision impairment in patients with diabetes mellitus type 2 [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients, OCT-A can reveal the enlargement of foveal avascular zone (FAZ), abnormalities in capillary flow density, and MAs, larger nonperfused areas, and neovascularization compared with controls. Studies have demonstrated more severe microvascular damage in DCP than in SCP in patients with DR [ 6 , 8 , 12 , 24 ]. However, OCT-A artifacts are common and often observed as motion or doubling artifacts in the deeper layers, due to shadows in moving blood cells in the overlying retinal vessels [ 18 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%